EFEKTIVITAS KEBIJAKAN KURSUS CALON PENGANTIN DALAM MENEKAN ANGKA PERCERAIAN DI WILAYAH KERJA KUA KECAMATAN TANJUNG BATU, OGAN ILIR, SUMATERA SELATAN - Agus Jaya; Muhammad Amin (Fakultas Syariah dan Ekonomi Islam, 2022)
This article is aimed to examine the effectiveness of the prospective bride and groom course policy in reducing the divorce rate in the work area of ​​the Office of Religious Affairs, Tanjung Bantu District, Ogan Ilir Regency, South Sumatra Province. Based on the results of the study, it can be concluded that the implementation of the prospective bride and groom course policy at the KUA Tanjung Batu District has been running since the issuance of the regulation although its implementation is still not optimal due to the lack of human resources, lack of facilities and lack of funds. Furthermore, the effect of the implementation of the prospective bride and groom course policy (suscatin) at the KUA Tanjung Batu District has had a positive influence in efforts to form a prosperous family and reduce the divorce rate in the KUA working area of ​​Tanjung Batu District as evidenced by the low percentage of complaints about divorce in the KUA Tanjung Batu District and the low percentage of cases going to the Kayu Agung Religious Court, but with improved facilities and maximum implementation the positive impact will be more visible and felt.